Społeczeństwo pod rządami żelaznej ręki w powieści "Moskwa 2042" Władimira Wojnowicza. Historyczny kontekst dystopii - Ochrem, Marek (Rusycystyczne Studia Literaturoznawcze, 2023)
In his article, Marek Ochrem discusses the issue of control over society in Vladimir Voinovich’s dystopian novel Moscow 2042 against the background of Aldous Huxley’s Brave New World and George Orwell’s 1984. The analysis focuses on methods of subordinating people to the will of the rulers and manipulating them. Ochrem is interested in the impact of the oppressive features of the fictional city-state on citizens: the cult of personality (Genialissimus), poor living conditions, the threat of deportation of dissidents, lack of access to information and entertainment, influencing the shape of the family, promoting universal spying, using religion for propaganda purposes, and censorship. Ochrem also shows analogies between the worlds of fictional dystopian and totalitarian regimes and actual ones.